A novel in‐capillary assay for dynamically monitoring fast binding between antibody and peptides using CE. Issue 24 (14th November 2018) - Wang, Jianhao; Qiu, Lin; You, Ying; Ma, Luping; Zhu, Zhilan; Yang, Li; Wang, Jianpeng; Wang, Xiang; Liu, Li; Liu, Xiaoqian; Chang, Yufeng; Li, Jie; et al.
Abstract: Nowadays, despite numerous techniques available for the detection of antibody–peptide binding, sensitivity and detection limit inflow still remains a major challenge. Herein, we report a strategy for the detection of binding inflow of monoclonal anti‐FLAG M2 antibody and 5, 6‐carboxyfluorescein‐labeled FLAG tag in capillary. Antibody and peptides were sequentially injected into the capillary where they mixed and bound together. Capillary electrophoresis with fluorescence detection was employed to monitor the binding process, and the results showed that the efficacy of the antibody–peptide binding in capillary (in‐capillary assay) is affected by the stoichiometry. Compared to the out‐capillary assay, this novel assay showed different K D values and required a very short detection time, thus showing great potential for rapid detection as well as other applications. Additionally, our novel assay can be used to investigate the stability of the antibody–peptide complex. The addition of excess DYKDDDDK or TAMRA‐DYKDDDDK, with similar binding priorities with M2, can leads to dissociation of the complex with a two‐step mechanism including dissociation and association. We believed that our developed method can be extended to monitor wide range of other biomolecule interactions.